Contribution to the Study of Diversity, Distribution, and Abundance of Insect Fauna in Salt Wetlands of Setif Region, Algeria - Djamila Mouhoubi; Rédha Djenidi; Mustapha Bounechada (International Journal of Zoology)
The present study aims to assess entomofauna biodiversity at three saline wetlands, located in Setif region, Northeastern Algeria. To determine the predominant environmental factors in the distribution of entomofauna, six different stations and three transects in each station were chosen according to the distribution of plant and soil salinity in each transect. Results were analysed, and different ecological indexes and analytical methods were applied, from 2016 to 2017. The total of individual insects belonging to 9 orders, 71 families, and 131 species were collected from the three sites. The highest abundance was in Coleoptera (38.17%) while the lowest abundance was found in Ephemeroptera (1.53%). The highest number of individuals (11438) was found in Bazer site in 2016, while the lowest number of individuals (4921) was in site Chott Frain in 2017. The highest abundance of insects (109) was recorded in transect BS1T16, and the lowest abundance of species was recorded in transect HS1T36. Diversity and equitability indices showed highest values in HS1T16 (H = 4,356) and HS1T37 (E = 0.7282). Some ecological parameters showed a significant relationship between the insects occurrence, distribution of plants, and type of soil.